THE ROLE OF THE LOCAL GOVERNMENT IN SUPPORTING SUSTAINABLE TOURISM (A CASE STUDY IN UBUD, GIANYAR REGENCY, BALI) - Sitohang, Lidya Lestari; Winulyo, Wahono Putra; Adib, Mohammad; Fitriani, Arza Nabila; Martin, Syrli; Zulfah, Zulfah (Pusat Penelitian dan Pengabdian Kepada Masyarakat Politeknik Pariwisata Bali, 2024)
Ubud, one of two sub-districts in Gianyar Regency, Bali, has been designated as a Tourism Area under the Regional Regulation of Bali Province. However, it is facing significant environmental challenges. It is of the utmost importance to address these issues in order to achieve sustainable tourism. The government is pivotal in establishing an environment conducive to the growth and sustainability of the tourism industry. This study empirically examines the role of the Ubud government in supporting sustainable tourism. A qualitative approach was employed, incorporating triangulation in the data collection process. Techniques such as interviews, observations, field notes, document analysis, and a literature review were used, and the data was analysed using thematic analysis. The findings suggest that the local government has implemented a top-down management system for sustainable tourism, with its roles encompassing public infrastructure acquisitor, strategic collaborator, policy regulator, and security and safety maintenance.